2010
DOI: 10.1016/j.mad.2010.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial oxidative damage and apoptosis in age-related hearing loss

Abstract: Age-related hearing loss (AHL) is a universal feature of mammalian aging and is the most common sensory disorder in the elderly population. Experimental evidence suggests that mitochondrial dysfunction associated with reactive oxygen species (ROS) plays a central role in the aging process of cochlear cells. Although it is well established that mitochondria are the major source of ROS in the cell, specific molecular mechanisms of aging induced by ROS remain poorly characterized. Here we review the evidence that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
113
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(119 citation statements)
references
References 84 publications
4
113
0
2
Order By: Relevance
“…Experimental evidence suggests that mitochondrial dysfunction associated with reactive oxygen species (ROS) plays a central role in the aging process of cochlear cells. 13 This was evidenced in the present study, in which we observed a significant increase in the level of Glutathione and a slight but significant decline in the SOD activity. A very high increase in the level of one antioxidant might have suppressed the activity of another antioxidant, SOD in the present study.…”
Section: Discussionsupporting
confidence: 73%
“…Experimental evidence suggests that mitochondrial dysfunction associated with reactive oxygen species (ROS) plays a central role in the aging process of cochlear cells. 13 This was evidenced in the present study, in which we observed a significant increase in the level of Glutathione and a slight but significant decline in the SOD activity. A very high increase in the level of one antioxidant might have suppressed the activity of another antioxidant, SOD in the present study.…”
Section: Discussionsupporting
confidence: 73%
“…Furthermore, the finding that shock startle responses of the CoQ-treated mice remained unchanged implies that the deleterious effects are related to the sensory rather than the motor component of the startle reflex. Age-related hearing loss has been associated with increased oxidative damage (Someya and Prolla 2010) and down-regulation of mitochondrial respiratory chain complexes which would lead to an excess production of oxidants (Someya et al 2007) in the cochlea. Previous studies have shown that altering the redox status of the cochlea affects hearing capacity, in particular caloric restriction has been shown to reduce presbycusis and attenuate oxidative damage .…”
Section: Discussionmentioning
confidence: 99%
“…Age-related hearing loss (AHL), characterized by a decline of auditory function with increasing age, is associated with attrition of spiral ganglion neurons and sensory hair cells in the cochlea of the inner ear (90,148). Studies have shown that CR delays the onset of AHL and reduces cochlear pathology (141,150) by reducing oxidative stress (150), which plays a major role in AHL (73,149).…”
Section: Sirt3 Prevents Hearing Loss During Crmentioning
confidence: 99%